Experimental And Numerical Studies On Thermal Analysis Of Heat Pipes For Computer Cooling Applications - Elnaggar, Mohamed H. A. (2012)
In computer industry, the growing development and demand for processing power necessitate efficient design of processors to conduct operations faster; consequently, the need for cooling techniques to dissipate the associated heat is quite obvious. Hence, it is highly desirable to explore high-performance cooling devices, especially for CPU cooling. In the present study, multi and twin U-shape vertical heat pipes, and single L-shape horizontal heat pipe, were investigated experimentally and numerically. Thermal analysis was performed under both natural and forced convection modes.